An Experimental Test of the Validity of Survey-Measured Political Ideology - Maite D. Laméris; Richard Jong-A-Pin; Rasmus Wiese (Center for Economic Studies and ifo Institute (CESifo), 2018)
We examine the predictive validity of survey-measured left-right political ideology by testing whether this measure is able to explain observed choices regarding equality versus efficiency. We study this in a real-effort distribution experiment, in which decision-makers allocate money equally or efficiently. We distinguish between decision-makers that receive `manna-from-heaven' and decision-makers that have earned the money to be distributed in a real effort task. We find that, conditional on entitlement concerns, self-reported right-wing ideology significantly predicts preferences for efficiency. Reported left-wing ideology does not have predictive value in explaining preferences for equality.
Keywords: C91; D31; 330; political ideology; survey measurement; predictive validity; distribution experiment; real effort